Hemotropic mycoplasma in a free-ranging black howler monkey (Alouatta caraya) in Brazil - Santos, Leonilda C.; Cubilla, Michelle P.; de Moraes, Wanderlei; Cubas, Zalmir S.; Oliveira, Marcos J.; Estrada, Marko; Leutenegger, Christian M.; Sykes, Jane E.; Lindsay, LeAnn L.; Marcondes, Mary [UNESP]; Filho, Ivan R. Barros; Biondo, Alexander W. (Wildlife Disease Association, 2013)
Hemotropic mycoplasmas are bacteria that infect erythrocytes and cause subclinical infections to life-threatening disease. We describe hemotropic mycoplasma infection in a free-ranging black howler monkey (Alouatta caraya). This is the first molecular detection of a hemotropic mycoplasma in a nonhuman primate from Brazil. © Wildlife Disease Association 2013.
Keywords: Alouatta; animal; animal disease; Brazil; case report; female; letter; microbiology; monkey disease; mycoplasmosis; wild animal; Animals; Animals, Wild; Female; Monkey Diseases; Mycoplasma Infections